2017
DOI: 10.1016/j.envpol.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and respiratory symptoms due to human exposure to polycyclic aromatic hydrocarbons (PAHs) in Kumasi, Ghana

Abstract: Studies of polycyclic aromatic hydrocarbons (PAHs) and its metabolites in PM10, soils, rat livers and cattle urine in Kumasi, Ghana, revealed high concentrations and cancer potency. In addition, WHO and IARC have reported an increase in cancer incidence and respiratory diseases in Ghana. Human urine were therefore collected from urban and control sites to: assess the health effects associated with PAHs exposure using malondialdehyde (MDA) and 8-hydroxy-2-deoxyguanosine (8-OHdG); identify any association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 63 publications
(75 reference statements)
1
23
1
Order By: Relevance
“…Extraction and analysis of urine sample for 8-OHdG followed the method described by Bortey-Sam et al (Bortey-Sam et al 2017). Briefly, urine (1 mL) was diluted with HPLC grade water (2 mL) after spiking with 25 ng/mL of (15N5) 8-OHdG (internal standard).…”
Section: -Hydroxy-2-deoxy-guanosine (8-ohdg)mentioning
confidence: 99%
“…Extraction and analysis of urine sample for 8-OHdG followed the method described by Bortey-Sam et al (Bortey-Sam et al 2017). Briefly, urine (1 mL) was diluted with HPLC grade water (2 mL) after spiking with 25 ng/mL of (15N5) 8-OHdG (internal standard).…”
Section: -Hydroxy-2-deoxy-guanosine (8-ohdg)mentioning
confidence: 99%
“…A number of studies have indicated that PAH metabolites may lead to oxidative stress and inflammation [ 8 , 9 , 10 , 11 , 36 ]. Several studies have shown that PAHs are ligands of aryl hydrocarbon receptors (AhR), and are able to activate these receptors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) classified BaP as carcinogenic to humans (Group 1) [ 6 ] and classified naphthalene as possibly carcinogenic to humans (Group 2B). Although many PAHs, including fluorene and phenanthrene, are undetermined due to a lack of investigations, exposure to PAHs brings out many other potentially harmful effects on human health [ 7 ], including oxidative stress [ 8 , 9 ], inflammation [ 10 , 11 ], cardiovascular disease [ 12 , 13 ], respiratory disease [ 14 ], and poor fetal development [ 15 ]. A cross-sectional study revealed that PAH metabolites, such as 2-hydroxyfluorene, 3-hydroxyfluorene, and 3-hydroxyphenanthrene, have a possible effect on rheumatoid arthritis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have investigated the toxic impacts related to the exposure to polycyclic aromatic hydrocarbons and volatile organic compounds. Polycyclic aromatic hydrocarbon substances, such as anthracene, phenanthrene, fluoranthene, benzo(a)pyrene, pyrene, and naphthalene, and many other forms are well-known to be the carcinogens for human health (Tongo et al, 2017, Sarigiannis et al, 2015, Bortey-Sam et al, 2017, Louis et al, 2016, Pham et al, 2013. On the other hand, volatile organic compounds also become hazardous chemicals and toxic to human health due to the carcinogenic and mutagenic characteristics (Kumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%